‘It’s Depend’, ‘Its Depend’, or ‘It Depends’? A Portrait of ELF Speaking Variations - Zainal Abidin, Zayani (J-Lalite: Journal of English Studies, 2024)
The present study aims to contribute to the existing knowledge on individual variation in situations where English is a lingua franca (ELF). In spoken conversations, it explores using two ungrammatical constructions, ‘it's + Vø’ (e.g., it’s depend) and ‘its + Vø’ (e.g., its depend). These constructions involve an uninflected present-tense singular verb form with it’s or its as subjects, which diverge from the standard -s inflected third-person singular with the pronoun it (e.g., it depends). This study examines the distribution of the variants of the ‘it's + Vø’ and ‘its+ Vø’ constructions and the factors influencing individual choice from an ELF environment. The data was from transcribed spoken texts of multilingual Asian English speakers in the Asian Corpus of English (ACE). The study identified 29 constructions from the idiolects of 20 individual speakers (4 males and 16 females) of various age groups, nationalities, and L1s. The analysis compared the individual use of the ungrammatical constructions, contracted form it’s in grammatical sentences, and present-tense markers (-s or zero) of singular verbs with singular subjects (he, she, it, this, and that). The findings suggest that ‘it's+ Vø’ and ‘its + Vø’ constructions of individual speakers are by the priming of it’s and zero inflection and chunking of idiomatic it's. The speakers exhibited interchangeability between these constructions and the present-tense markers of singular verbs with singular subjects.